Jamestown. The complete season 3 [videorecording (DVD)] - Gallagher, Bill (Screenwriter); Batt, Ben, 1986-; Queypo, Kalani, 1986-; Battrick, Naomi, 1991-; Colwell, Rachel (PBS Distribution, 2019)
1619. The British colony of Jamestown, Virginia, is shaken up when the first women in twelve years land in this breathtaking wilderness. While love triangles, bitter rivalries, and fierce competition cause conflict for the residents and the native inhabitants, the Pamunkey, they are bound together by their resolute will to survive and thrive in their new lives.